Secondary haemophagocytic lymphohistiocytosis in blood malignancies. The multicentre retrospective study - Vsevolod G. Potapenko; Alina S. Antipova3; Julia A. Zhuravleva; Yulia V. Zabutova; Alina Yu. Zavyalova; Irina V. Ishmatova; Elena V. Karyagina; Natalia A. Kotova; Valeria V. Kozyro; Tatiana G. Kulibaba; Daniil A. Manaenkov; Nadezhda V. Medvedeva; et al. (Clinical Medicine (Russian Journal), 2026)
Haemophagocytic syndrome (HPS) or haemophagocytic lymphohistiocytosis is a reaction of severe but ineffective inflammation. Blood malignancies (BlM) are among the frequent causes of HPS in adults. Objective. To analyse survival, causing trigger haemoblastosis, relationship with tumor and efficacy of including etoposide in chemotherapy of patients with secondary HPS-BlM. Material and methods. A retrospective analysis of case histories of patients with BlM complicated by SHPS was performed. The diagnosis of SHPS was verified using H-score and HLH-2004 criteria. Patients with both active malignant process and response to treatment were included in the study. Results. A total of 66 patients, median age 64 (19–90) years, 26 males and 40 females were included in the analysis. Of these, 44 (66.7%) had an active malignant process present. Overall survival in the SHPS-BlM group was 15.1% with a median of 2 (0.2–150) weeks. The prognosis was better in the group treated with etoposide than without it: three-week overall survival was 65.6% (n = 9) and 35%, respectively (p = 0.023). Median survival in the etoposide-free group was 1 (0.2–140) weeks. There were no diff erences in long-term survival depending on the presence of etoposide as part of chemotherapy. In patients without malignancy progression, a possible cause of SHPS was identified in only 8 (36.3%) patients. The overall survival rate was 18.1%, median 12 days (from 3 days to 150 weeks). Conclusion. The structure of patients with SHPS-BlM is dominated by patients with diff use B-cell large cell lymphoma. In the majority of patients SHPS is associated with progression, but in some patients VGFS activity persists despite the achievement of antitumour response. Inclusion of etoposide in therapy leads to an improved prognosis.